Effectiveness of the short-term use of Cimicifuga racemosa in the endothelial function of postmenopausal women: a double-blind, randomized, controlled trial. (3rd May 2020) - Fernandes, E. S.; Celani, M. F. S.; Fistarol, M.; Geber, S.
Abstract: Objective: This study aimed to assess the effects of daily use of Cimicifuga racemosa on endothelial function through flow-mediated dilation of the brachial artery, when used for 28 days by healthy postmenopausal women. Methods: The double-blind, randomized, placebo-controlled study included two groups of postmenopausal women ( n  = 31 each). The subjects were clinically assessed and flow-mediated dilation of the brachial artery was measured before and after 28 days of treatment. Patients received dry extract corresponding to 160 mg C. racemosa (extract with 4 mg of triterpene glycosides) or placebo. Results: Mean age, time since menopause, and body mass index in the two groups were similar. The measurements of flow-mediated dilation of the brachial artery, pre and post treatment, respectively, showed a significant increase in patients who used C. racemosa ( p  = 0.006), unlike patients who used placebo, who did not present changes in the outcome of flow-mediated dilation of the brachial artery after 28 days of use ( p  ≥ 0.05). When comparing the number of women in both groups who showed an increase in flow-mediated dilation, a significant difference was found in the measurements of the treated group after the use of the medication ( p  = 0.018). Conclusions: Daily use of 160 mg C. racemosa extract by postmenopausal women for 28 days beneficially influences endothelial function by promoting elasticity of the brachial artery.